Pragmatic Analysis Of Sarcasm In Tiktok Comments On Indonesian Political Issues - Pinta Ria Dewanti Zai; Menachem Gabriel Tarigan; Elsa Aprianti; Nala Annisa Danin (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
Sarcasm has become an increasingly prominent communicative strategy in online political conversations in Indonesia, especially on TikTok where public reactions to government policies spread rapidly and influence collective opinion. Although sarcasm frequently appears in digital political discourse, scholarly attention to its use within the Indonesian TikTok environment remains limited. This gap indicates the need for research that examines sarcasm not only as a linguistic style but also as a pragmatic act shaped by social and political context. Accordingly, this study analyzes the types and meanings of sarcasm expressed in user comments responding to Kompas.com’s TikTok posts about the 2025 DPR (House of Representatives) allowance policy.Employing a descriptive qualitative design, the study collected naturally occurring comments through documentation techniques. The comments were examined using classification of sarcasm and interpreted through pragmatic analysis. The findings identify seven comments that display various forms of sarcasm, including trait-based, action-based, result-based, directive, and label sarcasm. These sarcastic expressions function as tools for voicing criticism, conveying disappointment, and expressing social resistance toward the policy. They also reflect how TikTok users negotiate stance, construct collective sentiment, and articulate dissatisfaction within the digital public sphere. Overall, the study demonstrates that sarcasm serves as a powerful pragmatic mechanism in Indonesia’s online political communication. Through sarcastic remarks, users engage symbolically in political critique and participate in shaping public narratives surrounding governmental decisions. The results highlight the importance of examining sarcasm in digital platforms to better understand emerging forms of public expression, civic engagement, and socio-political commentary in contemporary Indonesian online discourse.